Development of holographic printed HOE recording technology with VHG-based FOV analysis for waveguide-type NED system - Hwang, Leehwan; Lee, Seunghyun (Frontiers in Physics, 2023)
We propose a holographic printing-recording technology for near-eye display through volume holographic grating analysis in hologram recording and reconstruction. Most near-eye displays are designed based on waveguide type and analog holographic optical elements, resulting in disruption of the uniformity of the image because of the difference between the initial recording conditions and the source image. This problem can be addressed using holographic printing technology to modulate different diffraction efficiencies for each holographic element. This study uses a digital HOE screen that can fabricate and reconstruct augmented reality images of 1.17”, 1.76”, and 2.35” in a field of view of 28.07°, 41.11°, and 53.13°, respectively, at a distance of 53.33 mm from the eye. Moreover, augmented images are realized with higher diffraction efficiency than conventional methods, simplifying the design and facilitating mass production of uniformed products using digital holographic printing technology.